2013
DOI: 10.1124/jpet.113.204040
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin or Lipopolysaccharide Treatment Modified Macrophage Populations after Colorectal Radiation of Rats

Abstract: Radiation-induced acute intestinal toxicity remains a major limitation to the delivery of tumoricidal doses of colorectal irradiation. Recent reports indicate that Toll-like receptor (TLR) agonists TLR4 and TLR5 protect against toxicity due to intestinal irradiation. The phenotype (M1 or M2) of macrophages expressing TLRs may play a role in tissue repair. The aim was to investigate whether administration of TLR4 agonist lipopolysaccharide (LPS) or TLR5 agonist flagellin after irradiation modified the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…The classic M1 phenotype of activated macrophages is induced by inflammatory cytokines including tumor necrosis factor (TNF)-α and interferon (IFN)-γ and by stimulation with bacterial constituents such as lipopolysaccharides (LPS) and flagellin or in response to an intracellular parasite infection [27,28]. M1 macrophages are characterized by the expression of a broad spectrum of proinflammory cytokines (TNF-α, interleukin (IL)-1β, IL-12, and IL-23) and chemokines (C-X-C motif chemokine (CXCL9, CXCL10, and CXCL11)) [19] (Table 1).…”
Section: Physiological Phenotypic Plasticity Of Macrophagesmentioning
confidence: 99%
“…The classic M1 phenotype of activated macrophages is induced by inflammatory cytokines including tumor necrosis factor (TNF)-α and interferon (IFN)-γ and by stimulation with bacterial constituents such as lipopolysaccharides (LPS) and flagellin or in response to an intracellular parasite infection [27,28]. M1 macrophages are characterized by the expression of a broad spectrum of proinflammory cytokines (TNF-α, interleukin (IL)-1β, IL-12, and IL-23) and chemokines (C-X-C motif chemokine (CXCL9, CXCL10, and CXCL11)) [19] (Table 1).…”
Section: Physiological Phenotypic Plasticity Of Macrophagesmentioning
confidence: 99%
“…While LPS can induce potent pro-inflammatory responses from macrophages in particular contexts, as discussed above LPS treatment of tumor macrophages following radiation therapy results in secretion of cytokines that are anti-inflammatory and support tumor growth and tissue repair 2729,65 . These data suggest that while LPS is a potent immune adjuvant, and while endogenous TLR4 adjuvants contribute to tumor control following radiation therapy, TLR4 ligation can have anti-inflammatory as well as proinflammatory effects, depending on the differentiation of the responding cells.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, because free radical generation has been shown to be elevated under conditions of low oxygen concentration (154), the presence of hypoxia may provide additional support for the role of oxidative stress in radiation injury. Furthermore, it has been suggested that the presence of both ROS and hypoxia regulates macrophage activation and polarization (155, 156), conditions shown to be associated with late radiation injury (148, 157). …”
Section: Countermeasure Efforts: Targets/approaches/alternativesmentioning
confidence: 99%